2011
DOI: 10.1007/s11418-011-0535-9
|View full text |Cite
|
Sign up to set email alerts
|

Adaptogenic potential of curcumin in experimental chronic stress and chronic unpredictable stress-induced memory deficits and alterations in functional homeostasis

Abstract: The present study was designed to investigate the role of curcumin in chronic stress and chronic unpredictable stress-induced memory deficits and alteration of functional homeostasis in mice. Chronic stress was induced by immobilizing the animal for 2 h daily for 10 days, whereas chronic unpredictable stress was induced by employing a battery of stressors of variable magnitude and time for 10 days. Curcumin was administered to drug-treated mice prior to induction of stress. Body weight, adrenal gland weight, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 54 publications
(42 reference statements)
1
22
0
1
Order By: Relevance
“…There were no differences in thymus weights between running and sedentary mice (Figure 3b). These findings are consistent with the results of others in demonstrating that wheel running in C57BL/6J mice produces adrenal enlargement consistent with HPAaxis activation (Droste et al, 2003) without the thymal involution typically observed alongside adrenal enlargement in stressed animals (Bhatia et al, 2011;Kour and Bani, 2011;Réus et al, 2012).…”
Section: Methodssupporting
confidence: 93%
“…There were no differences in thymus weights between running and sedentary mice (Figure 3b). These findings are consistent with the results of others in demonstrating that wheel running in C57BL/6J mice produces adrenal enlargement consistent with HPAaxis activation (Droste et al, 2003) without the thymal involution typically observed alongside adrenal enlargement in stressed animals (Bhatia et al, 2011;Kour and Bani, 2011;Réus et al, 2012).…”
Section: Methodssupporting
confidence: 93%
“…To additionally clarify the decreased testosterone levels, the disturbances of other steroidogenic machineries such as cytochrome P-450 cholesterol side-chain cleavage enzymes, * P<0.05, compared with the control group scavenger receptor class B, and hydroxysteroid dehydrogenases need to be further investigated. In various studies, the increase of malondialdehyde levels and the decrease of enzymatic activities of catalase, glutathione, and superoxide dismutase have been demonstrated in stress testicular tissue (Zayachkivska et al, 2006;Brzozowski et al, 2008;Bhatia et al, 2011;Warzecha et al, 2011;Kwiecien et al, 2012;Hari Priya and Sreenivasula Reddy, 2012;Xu et al, 2014). The alteration of oxidative stress markers might affect normal spermatogenesis, resulting in decreased sperm concentration (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, the corticosterone levels are markedly elevated under a restraint immobilization condition (Bhatia et al, 2011;Prabsattroo et al, 2015). Corroborated with the decrease of testosterone levels, Lin et al (2014) demonstrated that stress could decrease the expression of steroidogenic acute regulatory (StAR) protein and the cytochrome P450 side chain cleavage enzyme (CYP11A1) in rat Leydig cells after acute immobilization stress induction.…”
Section: Introductionmentioning
confidence: 95%
“…suspended in 0.5% aqueous solution of carboxymethyl cellulose 30 min before induction of ulcer. The dose was selected based on our preliminary experiments and the findings of Bhatia et al [14]. All groups received equivalent volumes of the above-mentioned vehicles.…”
Section: Methodsmentioning
confidence: 99%